Integrative approach to designing the content of secondary specialized vocational education - Mukhayo K. Baybaeva, Zukhra K. Ismailova, Dustnazar O. Khimmataliev, Masuda K. Khashimova,; Ergashev, Bobirjon B. (Opción, 2020)
The article discusses the issues of integrated approaches to the design of software content for vocational education. The study was conducted using the method of abstraction, ascent from the abstract to the concrete; logical analysis of scientific literature on the topic of the article; descriptive and diachronic. As a result, the integration of the learning process contributes to comprehensive learning, allows us to develop logical and figurative thinking in equal parts, supports rational and emotional areas of activity and ensures their unity. In conclusion, the need for integration is to bridge the boundaries between fields of science.